Biochemical and Molecular Evaluation of Some Tomato Hybrids in Salt Stress At The Growth Stage - ULUIŞIK, Selman; KABAS, Aylin; CELIK, Ibrahim (ISPEC Journal of Agricultural Sciences, 2022)
Growing stages of plants are the most sensitive phase to abiotic stress which leads to decrease in yield. The object of this study was to evaluate the biochemical and molecular properties of seven tomato cultivars and to observe their responses to salinity during growth stages. Greenhouse experiment was performed to study differences in genotypes response to salinity with four doses (50 mM, 100 mM, 150 mM and 200 mM). Differences in growth parameters, proline accumulation, lipid peroxidation and hydrogen peroxide were tested in order to put forward the relative tolerance or sensitivity of tomato cultivars. These results were also supported by expression using semi quantitative RT-PCR of two stress related genes, SIVOZ1, and SIWRKY8. Overall results demonstrated that, all evaluated parameters increased with 200 mM NaCI treatment for all cultivars. Although the effects of salinity stress differentiated in different genotypes, our results provided some evidence that Seyran, Ciko and Indigo Rose Black tomato cultivars had higher salt tolerance potential than rest of the cultivars. This is the first report of evaluation of Turkish tomato hybrids based on biochemical and molecular data and results could be useful for determination of future breeding strategies for salt tolerance in tomato.